Impact of the COVID-19 Pandemic on Construction Industry in Malaysia - Mohsen, A. (Institute of Electrical and Electronics Engineers Inc., 2021)
The world has a corona virus epidemic and Malaysia does not have an immune system. The Covid-19 epidemic causes considerable global disruption in an effort to stop this spread, leading to lockups in various countries, including Malaysia. The Malay Government proposed the Movement Control Order on 18 March 2020 in its lock-out option (MCO). Malaysian companies were therefore heavily affected by the MCO in this particular construction industry. There is a strong influence on the economy of the country. The epidemic of COVID-19 affected the global financial market, Malaysia, and others. The aim of this study is to analyze the construction industry, project budget, contractual arrangements, construction occupational health and safety, and other relevant factors in the construction industry, with the objective of examining the impacts and challenges facing the Malaysian construction industry. The results of this study could help stakeholders understand the impact of COVID-19 on Malaysia's various industries. The results indicate that the construction industry has faced numerous challenges including time periods, interrupted revenues, deferred licenses, travel bans, significant health and safety concerns and labor and equipment deficiencies, among other issues, all of which have affected the timely delivery of projects in the area of infrastructure. This also illustrates that Malaysian governments and construction agencies have taken steps to protect the construction industry against negative effects of the pandemic, such as financial support programmes, the digitalization of processes, service charges and fees, medical centers, and other contract mediation services. Â© 2021 IEEE.